Evaluation of GPM Dual-Frequency Precipitation Radar Algorithms to Estimate Drop Size Distribution Parameters, Using Ground-Based Measurement over the Central Andes of Peru - Del Castillo-Velarde, C. (2021)
The present study comes under the project “MAGNET-IGP: Strengthening the research line in physics and microphysics of the atmosphere (Agreement No 010-2017-FONDECYT)”. Yamina Silva-Vidal, Jose Luis Flores-Rojas and Jairo Valdivia-Prado would like to acknowledge the Peruvian PPR068 programme "Reducción de vulnerabilidad y atención de emergencias por desastres" for financial support of their work. This work was done using computational resources, HPC-Linux -Cluster, from Laboratorio de Dinámica de Fluidos Geofísicos Computacionales at Instituto Geofísico del Perú (Grants 101-2014-FONDECYT, SPIRALES2012, IRD-IGP, Manglares IGP-IDRC, PP068 program).